Analysis of students’ higher order thinking skills in solving basic combinatorics problems - Wilfridus Beda Nuba Dosinaeng (Math Didactic: Jurnal Pendidikan Matematika, 2019)
This is a case qualitative study that aims to describe students’ ability in solving basic combinatorics problem with higher order thinking skills. The subjects of this study were three students of mathematics education study program consisting of one high-ability student, one medium-capable student, and one low-ability student selected purposively. This study was conducted by analysing the critical and creative thinking skills of the students in solving counting rules, permutation, and combination problems. In terms of critical thinking skills, the results of this study showed that the students' self-regulation ability were still low. Their critical thinking skills in general were still limited to the interpretive and analytical ability. Only high-ability student showed the problem evaluation ability. However, the three students were unable to realize the mistake in their designed strategy for problem solving because they still have low-self regulation ability. Meanwhile, in terms of the creative thinking skills, the three students were able to produce original ideas in solving basic combinatorics problems though the high-ability student was better compared to the other two. However, their low level of flexible thinking ability as well as their low ability of self-regulation prevent them from producing different ideas.